2004
DOI: 10.1097/01.ede.0000142138.46167.69
|View full text |Cite
|
Sign up to set email alerts
|

Parental Age, Family Size, and Risk of Multiple Sclerosis

Abstract: Parents who have offspring with MS may have subtly impaired fertility. The unexpected association with paternal age may be the result of an increased risk of accumulating germ cell mutations among older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
37
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 34 publications
6
37
2
Order By: Relevance
“…Nonetheless, children of older fathers are not only more likely to have several diseases of clear genetic cause (Kühnert and Nieschlag, 2004;Lambert et al, 2006), they show also an increased risk for multifactorial diseases such as birth defects (Olshan et al, 1994;McIntosh et al, 1995;Kazaura et al, 2004;Bille et al, 2005;Zhu et al, 2005a, b;Archer et al, 2007;Yang et al, 2007), childhood cancers (Moll et al, 1996;Hemminki et al, 1999;Sharpe et al, 1999;Murray et al, 2002;Yip et al, 2006), prostate cancer (Zhang et al, 1999), breast cancer (controversial) (Colditz et al, 1991;Choi et al, 2005), diabetes mellitus type l (Bingley et al, 2000;Cardwell et al, 2005), multiple sclerosis (Montgomery et al, 2004), some forms of cerebral palsy (Fletcher and Foley, 1993), schizophrenia (Malaspina, 2001), bipolar disorder (Frans et al, 2008), autism (Reichenberg et al, 2006), epilepsy (Vestergaard et al, 2005), Alzheimer disease (Whalley et al, 1995) and lower intelligence quotients (Malaspina et al, 2005;Saha et al, 2009). However, some of the reported associations need to be considered with caution for methodological reasons in the statistical analysis, especially in regard to the validity of the data sources (Kirby, 2007) (Fig.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 99%
“…Nonetheless, children of older fathers are not only more likely to have several diseases of clear genetic cause (Kühnert and Nieschlag, 2004;Lambert et al, 2006), they show also an increased risk for multifactorial diseases such as birth defects (Olshan et al, 1994;McIntosh et al, 1995;Kazaura et al, 2004;Bille et al, 2005;Zhu et al, 2005a, b;Archer et al, 2007;Yang et al, 2007), childhood cancers (Moll et al, 1996;Hemminki et al, 1999;Sharpe et al, 1999;Murray et al, 2002;Yip et al, 2006), prostate cancer (Zhang et al, 1999), breast cancer (controversial) (Colditz et al, 1991;Choi et al, 2005), diabetes mellitus type l (Bingley et al, 2000;Cardwell et al, 2005), multiple sclerosis (Montgomery et al, 2004), some forms of cerebral palsy (Fletcher and Foley, 1993), schizophrenia (Malaspina, 2001), bipolar disorder (Frans et al, 2008), autism (Reichenberg et al, 2006), epilepsy (Vestergaard et al, 2005), Alzheimer disease (Whalley et al, 1995) and lower intelligence quotients (Malaspina et al, 2005;Saha et al, 2009). However, some of the reported associations need to be considered with caution for methodological reasons in the statistical analysis, especially in regard to the validity of the data sources (Kirby, 2007) (Fig.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 99%
“…This association was profound in breast cancer cases in premenopausal women (OR51.9 for paternal aged o40 years vs. ,30 years) (P (for trend)50.031). In a retrospective analysis using the Swedish Inpatient Register, Montgomery et al 103 identified 4443 patients with a diagnosis of multiple sclerosis. Twenty-four thousand, one hundred and ninety-four controls were selected with similar characteristics for year, county of birth and survival until at least the age at diagnosis of the matched cases.…”
Section: Other Conditionsmentioning
confidence: 99%
“…higher birth order indicating the influence of older siblings, other aspects of sibship structure and day care attendance) are associated with a reduced risk of atopic disorders [6]. However, for multiple sclerosis (MS), although higher younger sibling exposure has been associated with reduced MS risk [7,8] including in this study sample [8], the pattern for older siblings or birth order is less clear [9]. Here we examine the association between asthma, MS and sibling exposure in a population-based case-control study.…”
Section: Introductionmentioning
confidence: 99%